Sociocultural factors influencing the production and consumption of fruits and vegetables in Boukoumbé in Northern Benin. - Bankole, Malikath; Bodjrenou, Sam; Houndolo, Melina; Termote, Celine; Chadare, Flora; Amoussa Hounkpatin, Waliou (2023)
Presented at the 5th International Congress Hidden Hunger, 4–6 September 2023, Hohenheim, Germany. Fruits and vegetables (F&V) are vital for healthy diets, with a broad consensus that a diversified diet containing a range of plant foods is needed for health and well-being. Although the African continent is considered to have a huge diversity of F&V, we are witnessing a decrease in the production and use of some of them. This study investigated the reasons behind the low production and use of some F&V species in the commune of Boukombé in the Atacora department, this commune is one of the most food insecure in Benin. Qualitative approach especially the snowball method has proceeded to select the key informants constituted of market gardeners and institutions involved in agriculture in Boukombé. The 4-cells method was used to collect information about production and consumption and then semi-structured interviews as well as focus group discussions were used to better understand the perceptions of the market gardeners. Fruits and vegetables were the most represented species with respectively 34.6 % and 27 % of species available. About 60 % of F&V species identified were perennial while 40 % were annual and most of them were cultivated by the population. Only 28 % were grown wildly in nature and few were semi-cultivated. Among the species cultivated, many were identified as being grown in a small area by a few people and as being consumed by a small number of people occasionally. The main reasons that explain this low production were essentially the inaccessibility of roads from villages to markets, the perishability of F&V, the soil poverty, the lack of water sources because those villages are located on the mountains, and the high seed prices of some F&V such as carrots, cabbage, and lettuce. This induced a low consumption of these species which were lowly available in the environment. In addition, there were the deforestation practices and then, the lack of knowledge about the conservation of F&V species, as well as their market value which made populations prioritise their sale over their consumption. Meanwhile, several strategies were proposed including the establishment of community seed banks to improve the production and consumption of F&V species in their community.